IMPROVEMENT OF THE QUALITY OF SERVICE IN THE DEVELOPMENT OF THE HEALTH RESORT AND RECREATIONAL SECTOR OF UKRAINE - Tsohla, Svitlana (Journal of European Economy, 2017)
The analysis of the satisfaction level of health resort rest is conducted. The «price-quality» econometric models for the rest homes and health resorts in order to define the service quality level for the health resort regions are developed. The improvement trends of target-oriented development of resort and recreational sector are proved.